A Simple Treatment of Tannery Wastewater using Modified Activated Carbon by Metal Chloride - Kistan, A.; Premkumar, A.; Kanchana, V. (Asian Journal of Chemistry, 2022)
Tannery wastewaters are exceedingly complex and characterized by high contents of organic, inorganic and nitrogenous compounds, chromium, sulfides, suspended solids and dissolved substances. Treatment of tannery wastewater was carried out by using activated carbon modified metal chlorides approaches. Effluent from an existing tannery was used as the test medium. The characteristics of the influent and effluent after the chemical treatment were determined. Modified activated carbon mixed with clarified tannery effluent then the various constituents of the effluent were re-investigated. The results indicated a very good deduction of physico-chemical parameters and heavy metals such as chromium were gradually reduced with the introduction of 100-500 mg/L of activated carbon metal chlorides, including CaCl2, which were 41% (EC), 76% (BOD), 47% (COD) (72%) (TDS), 87% (total hardness), 45% (chlorides), 63% (sulphate), 58% (nitrates), 70% (Cr), 32% (surfactants).